INDICANUTRI LP: aplicativo de gestão de indicadores nutricionais de pacientes com lesão por pressão - Barrios, Weruska Davi [UNIFESP] (2018)
Introduction: The diet therapy is important to ensure the nutrients supply, duo to the therapeutic role in chronic and acute diseases. Monitor inpatient nutritional indicators and early intervention has a major impact not only in the improvement of their nutritional status, as well as in the hospitalization cost. Health professionals have already used tools such as the internet, software and applications as a vehicle. Objective: Develop an application for nutritional indicators management in hospitalized patients with pressure ulcer. Method: From September to November 2017; it was conducted a search in Google Play® application store and used Design Thinking methodology to develop the app prototype, through experts consulting such as: nutrition specialist, nursing and hospital managers. Results: It was found 248 applications in the prior art search in different categories that were not relevant to the subject of this study. A questionnaire was given to 31 experts as the first stage of Design Thinking and showed that 94% record their data manually, using 2 to 5 professionals in this activity. Conclusion: It was developed INDICANUTRI LP® - an application for nutritional indicators management for patients with pressure ulcer.